Vitreopapillary Traction Causing Optic Nerve Head Elevation - Mohamed M. Khodeiry; Mohammad Ayoubi; Christopher A. Dorizas; Carlos E. Mendoza-Santiesteban; Maja Kostic (Case Reports in Ophthalmological Medicine)
Conclusions and Importance: This case highlights the importance of clinical examination and ancillary testing in differentiating etiologies of optic disc elevation.